Figurative Language Analysis In Emily Dickinson’s Poem “Hope Is The Thing With Feathers” - Aprilia Aprilia; Naifa Safina Amalia (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
This article explores how Emily Dickinson uses figurative language in her poem “Hope is the Thing with Feathers.” Using qualitative descriptive analysis methods, this research delves into how Emily Dickinson employs figurative language in her poem. various forms of Figurative Language contained in the poetry, such as Metaphor, Personification, Irony, Symbolism and Hyperbole was found in the poem. Research findings show that Dickinson’s use of Figurative language deepens the poem’s meaning and emotional impact, potraying hope as a pure force that seeks no reward and remains within the human soul, even in toughest of times. The authors identified five types of figurative languages in the poem; metaphor, personification, irony, symbolism, and hyperbole. This provides an in-depth look at how Figurative Language is use to depict abstract themes creatively and enhance the emotional effect on the reader.